The Decrease in Number and Change in Phenotype of Mucosal‐Associated Invariant T cells in the Elderly and Differences in Men and Women of Reproductive Age. (October 2014) - Novak, J.; Dobrovolny, J.; Novakova, L.; Kozak, T.
Abstract Mucosal‐associated invariant T (MAIT) cells are innate‐like T cells comprising up to 10% of the peripheral blood T cells in humans. During ontogeny, MAIT cells can first be detected in the cord blood in low amounts, but rise steadily after birth. In this population‐based study, we show that their counts continue to increase, reaching maximal levels (4.5% of CD3+ cells, 65 cells/μl) in the third and fourth decenniums. At this age, the amounts of MAIT cells exhibit the highest interindividual variability. The values then dramatically decline; subjects 80 years old and older have on average 10 times less MAIT cells, both absolutely and as a percentage among CD3+ T cells, than subjects in fertile age. The senescence of MAIT cells is associated with decreased CD8/double negative (DN) ratio. Finally, we observed significantly higher amounts of MAIT cells in women of reproductive age than in men of the same age. Our data suggest that further studies aimed at elucidating a role of MAIT cells in human pathologies must recruit age‐ and gender‐matched controls.